Tantangan dan Strategi Mahasiswa Manajemen dalam Memahami Materi Perkuliahan Online - Hendestri Br Sembiring; Cynthia Ananda Br Tarigan; Naila Suci Yanti; Nayla Humaimah; Siti Suaibah Nasution (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to examine the challenges and strategies of Management Study Program students at the State Islamic University of North Sumatra (UINSU) in understanding online lecture materials. The method used is descriptive qualitative with data collection techniques in the form of closed questionnaires distributed to 25 respondents of fourth semester students. The results showed that although there were still technical problems such as unstable internet connections, the majority of students were able to adapt to the online learning system. The most dominant learning strategies used are active and independent strategies, such as reading, taking notes, repeating material, watching learning videos, and managing study time. In addition, group discussions through media such as WhatsApp and Telegram also help clarify understanding of the material. Students also rely on learning materials provided by lecturers through digital platforms (PDF, video, and LMS) as the main source of independent learning. This study concludes that students' success in understanding online lecture materials is strongly influenced by a combination of active learning strategies, group collaboration, and material support provided by lecturers. Therefore, continuous collaboration between students, lecturers, and institutions is needed to create a more effective and inclusive online learning system.